Ideology-loaded national sustainability discourse: An eco-linguistic Analysis - Abdelraouf, Mohamed Abdelfattah; Elewa, Abdelhamid (Research Journal in Advanced Humanities, 2026)
This study investigates how the environmental sustainability ideology of Saudi Vision 2030 is constructed and reproduced in the Saudi secondary school Ecology textbook. Drawing on van Dijk’s socio‑cognitive model of Critical Discourse Analysis and Stibbe’s ecolinguistic framework, it examines lexicalization, agency, framing, pronoun use, and patterns of evaluation in the textbook discourse. Lexical analysis shows that the textbook consistently evaluates ecosystem sustainability positively and environmentally degrading activities negatively, while promoting conservation on religious, aesthetic, and economic grounds. These choices align the text with Vision 2030’s largely neoliberal–anthropocentric environmental perspective and help shape students’ mental models in ways that make this perspective appear both rational and morally justified. The study contributes to ecolinguistics and critical education research by showing how a national transformation plan with strong environmental elements is translated into educational discourse, and it provides insights to curriculum designers, policymakers, and teachers concerned with environmental education.